Congenital Epulis : Report of Two Cases - Shilpa J Parikh; Madhura Jain (Wolters Kluwer Medknow Publications, 2005)
Congenital epulis of the newborn is a rare tumor of infancy. It occurs more often in female that in males and in the maxilla more than in the mandible. Various theories of its origin have been described. Here two cases of congenital epulis are presented. Case one is an unusual case of congenital epulis involving alveolar mucosa of maxilla and mandible in a girl and case two is the single congenital epulis involving alveolar mucosa of mandible in a boy is reported.